Diaquabis(N,N-diethylnicotinamide-κN (1))bis(4-formylbenzoato-κO (1))zinc - Sertçelik, Mustafa (International Union of Crystallography, 2012)
In the title complex, [Zn(C(8)H(5)O(3))(2)(C(10)H(14)N(2)O)(2)(H(2)O)(2)], the Zn(II) cation is located on an inversion center and is coordinated by two 4-formylbenzoate anions, two N,N-diethylnicotinamide (DENA) ligands and two water molecules. The four O atoms in the equatorial plane around the Zn(II) cation form a slightly distorted square-planar arrangement, while the slightly distorted octahedral coordination is completed by the two N atoms of the DENA ligands in the axial positions. The dihedral angle between the carboxylate group and the adjacent benzene ring is 2.96 (11)°, while the pyridine ring and the benzene ring are oriented at a dihedral angle of 79.26 (4)°. The coordinating water molecule links with the carboxylate group via an intramolecular O—H⋯O hydrogen bond. In the crystal, O—H⋯O and weak C—H⋯O hydrogen bonds link the molecules into a three-dimensional supramolecular network. A π–π contact between the parallel pyridine rings of adjacent molecules may further stabilize the crystal structure [centroid–centroid distance = 3.5654 (8) Å].